Gadachrili Gora: Architecture and organisation of a Neolithic settlement in the middle Kura Valley (6th millennium BC, Georgia). (22nd February 2016) - Hamon, Caroline; Jalabadze, Mindia; Agapishvili, Tata; Baudouin, Emmanuel; Koridze, Irakli; Messager, Erwann
Abstract: The mechanisms responsible for the emergence of a farming economy in Transcaucasia have been the subject of much debate since the 1970's. This debate has focused particularly on the role played by Near-Eastern influences in the development of the Shulaveri-Shomu culture, which emerged in the Kura Basin at the end of the 7th millennium BC. Recently, archaeological investigations have been conducted by a Georgian-French team in Gadachrili Gora, one of four "Shulaveri group" tells located on a tributary of the Chrami River in the Kvemo-Kartli plain of Georgia. Dating evidence clearly places the first levels of this tell in an early phase of the development of the culture, between 5920 and 5720 Cal BC. These investigations provide new evidence regarding the processes of neolithisation, especially in terms of settlement organisation and the architectural techniques used at the time. Several occupation levels feature connected circular units, of various sizes, together with "courtyards", which were used as circulation – or waste disposal areas. The density and organisation of these structures display different patterns for the two distinct levels of occupation preserved. Evidence from the deepest occupation levels suggests a high density of occupation in the settlement, with complex episodes of destruction and rebuilding. Several building techniques were used, including different types of bricks laid in various patterns depending on wall types. In addition, there is evidence for the use of the "bauge" construction technique, which was unknown in the region until now. Parallels established with the construction techniques of Northern Iran and Mesopotamia contribute to the discussion regarding the processes underlying the emergence of the Shulaveri culture. Moreover, the high number of storage structures and the discovery of organized built spaces dedicated to storage raise many questions about the status of the site, the organisation of agricultural practices, and the relationship of these populations to the hydrographic network within the area.